IMPLEMENTATION OF ENVIRONMENTAL RESPONSIBILITY IN THE PRACTICE OF THE MANAGEMENT OF DOMESTIC ENTERPRISES - O. Grishnova; O. Brintseva (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The essence of environmental responsibility as part of CSR is proved in the article. The general evaluation of the most significant environmental problems in Ukraine is given. The lack of interest in environmental protection in domestic business is identified (it’s indicated by the rapid increase in costs of utilities to pay the environmental tax, while the rate of growth of capital and current expenditure on environmental protection is minimal). The estimation of the level of implementation of environmental responsibility in the management practices of leading Ukrainian companies according to their non-financial reports is proved. The evaluation of environmental indicators by the standard GRI in reports of socially responsible companies are performed. The extremely low level of implementation of environmental responsibility in the practice of management of companies – ranking leaders at CSR in Ukraine is determined. The necessity of improving the environmental responsibility at all levels is substantiated.